PERENCANAAN INSTALASI PENGELOLAHAN AIR LIMBAH MA 2 ANNUQAYAH KECAMATAN GULUK-GULUK KABUPATEN SUMENEP - RAHMANTO, ACH. DESMANTRI (NAROTAMA JURNAL TEKNIK SIPIL, 2022)
MA 2 Annuqayah has increased the number of students in the last 5 years. Based on this, the MA 2 Annuqayah institution took the initiative to build a new infrastructure for a two-story school building. Along with the construction of a two-story school building, a Waste Water Treatment Plant (IPAL) planning is also needed. For the location of MA 2 Annuqayah, it is located in Guluk-Guluk District, Sumenep Regency. The purpose of this study is how to plan a wastewater treatment plant using a septic tank, control tank, infiltration field and the drawing design along with a budget plan (RAB). raise awareness of the dangers of domestic wastewater. The method used is descriptive method using a quantitative approach in the form of data collection in the form of numbers according to facts or reality in the field. Septic tank capacity for 200 people with wet room volume: 48 m3, mud room volume: 18 m3 and free threshold volume: 13.5 m3 with the required budget for planning in MA 2 Annuqayah Rp. 107,831,000.00